1989
DOI: 10.1007/bf02546062
|View full text |Cite
|
Sign up to set email alerts
|

Deacidification of olive oils by supercritical carbon dioxide

Abstract: An investigation of the application of supercritical carbon dioxide (SC‐CO2) extraction to the deacidification of olive oils has been made to verify that the nutritional properties of the oil remain unchanged when this technique is applied.Preliminary runs at 20 and 30 MPa in the temperature range of 35–60°C were performed on fatty acids and triglycerides as pure compounds or mixtures, to determine their solubility in SC‐CO2. The solubility data obtained show that CO2 extracts fatty acids more selectively than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
2

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 10 publications
3
36
0
2
Order By: Relevance
“…As mentioned above, pressure and density have a close relation, and the extraction effect becomes higher when pressure is high. Several authors have investigated the extraction and purification of lipid compounds, such as triacylglycerols, free fatty acids, and sterols, using scCO 2 [29]- [33]. It is anticipated that lower molecular weight polymer chains are extracted properly at 14 MPa, and it seems that the oil which dissolved in the scCO 2 effectively replace shorter polymer chains, and is impregnated.…”
Section: Effect Of Pressure On Impregnation Of Poly(l-la) Random Copomentioning
confidence: 99%
“…As mentioned above, pressure and density have a close relation, and the extraction effect becomes higher when pressure is high. Several authors have investigated the extraction and purification of lipid compounds, such as triacylglycerols, free fatty acids, and sterols, using scCO 2 [29]- [33]. It is anticipated that lower molecular weight polymer chains are extracted properly at 14 MPa, and it seems that the oil which dissolved in the scCO 2 effectively replace shorter polymer chains, and is impregnated.…”
Section: Effect Of Pressure On Impregnation Of Poly(l-la) Random Copomentioning
confidence: 99%
“…Despite its higher FFAs, they found that Folch-extracted oil revealed much better oxidative stability as the polar solvent was able to extract the phospholipids that acted as a synergist for the primary antioxidant present in crude oil (tocopherols). It has been also reported the SFE oils showed significantly higher FFAs content than their solvent-extracted counterparts; however the high amounts of FFAs were not considered an indication of increased hydrolysis during extraction procedure, but are due to poor recovery [21,47,48].…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…Ooi et al (1996) decreased the FFA content of palm oil to 0.1% in a continuous SC-CO 2 extractor. Brunetti et al (1989) obtained deacidification of high acidic olive oil with SC-CO 2 at pressures of 20 and 30 MPa, and temperatures of 40 and 60 °C. They reported that the selectivity for FFAs was highest at 20 MPa and 60 °C.…”
Section: Deacidificationmentioning
confidence: 98%